Contigency Analysis in Multiline Distributed System using Dynamic Voltage Restorer. Issue 1 (December 2020) - Antony Charles, A; Joshua Jeyasekar, D; Ramya, G; Suresh, P; Manimaran, B
Abstract: Power system security analysis involves a vital role in improving the system security and helps preventing the system collapse condition. This paper shows the conception and simulation of nine bus system with generator outage contingency. The objective of this work is to improve the real and reactive powers by employing DVR. Nine bus systems with generator outage contingency condition healthy, unhealthy without IDVR and unhealthy with DVR are simulated. The comparative study is presented to demonstrate the improvement in the power quality by adding DVR. The results indicate that real and reactive powers are improved by adding DVR.